Pilot Study: The Effect of Acute 5-Day Creatine Supplementation on Macrovascular Endothelial Function in Older Adults. (29th May 2020) - Clarke, Holly; Kim, Do-Houn; Meza, Cesar; Hickner, Robert
Abstract: Objectives: Cardiovascular disease (CVD) remains the leading cause of mortality in the United States, and aging is a primary risk factor for CVD events. Dietary creatine supplementation has been used to alleviate age-related health deteriorations, and has been shown to reduce sarcopenia, improve cognition and decrease reactive oxygen species in older adults. There is scarce information, however, regarding the use of creatine to improve vascular function. Therefore, the primary aim of this pilot study was to determine the effect of creatine on vascular function in older adults. Methods: Four older adults (66 ± 8.3 years) participated in this pilot study, with four young adults (27 ± 2.9 years) serving as a comparator. Participants reported for their baseline visit, and completed basic anthropometrics and resting hemodynamic testing. Brachial artery flow mediated dilation (FMD) was used to assess macrovascular endothelial function following 5-minutes of occlusion. Resting and peak brachial artery diameters were assessed using edge detection software, and FMD % change (FMD%) was determined utilizing the following equation: [(peak diameter – baseline diameter)/baseline diameter] * 100. Participants were then given creatine monohydrate to consume over the following 5 days (4 × 5 g/day), before returning to repeat all assessments. A two-way ANOVA statistical analysis was performed using SPSS software, and significance was accepted at P   ≤  0.05. Results: No statistically significant changes were seen in FMD%. However, mean delta (Δ) change for groups did show a greater improvement in FMD% in old vs. young (Δ2.44 ± 1.78% vs. −.82 ± 3.09%) and estimated marginal means of FMD showed a positive change in FMD% in older adults but not in younger. Furthermore, 100% of older adults showed improvement following creatine, whereas only 50% of young adults showed (minimal) improvement. Conclusions: Although there were no significant changes identified, this may be due to the small sample size not being sufficient to detect an interaction effect. The improvements seen for each older adult could still be considered physiologically significant for vascular health, and future study of additional participants may result in significant benefits and expand the use of creatine to improve vascular health. Funding Sources: No grants or Funding Sources were used for this pilot study.